ENGLISH FRICATIVE ACQUISITION AMONG UZBEK EFL LEARNERS: A SYNTHESIS AND THEORETICAL REINTERPRETATION (SCIENCE TIME JOURNAL, 2026)
. This article re-examines previous findings on Uzbek English as a foreign language (EFL) learners’ acquisition of English fricatives, with particular attention to interdental fricatives /θ/ and /ð/ and their relationship to alveolar and postalveolar fricatives. Rather than presenting a new experimental dataset, the article develops a professional synthesis and theoretical reinterpretation of two related studies: a focused 2024 study on the production and perception of English interdental fricatives by native Uzbek speakers and a later dissertation-based investigation of six English fricatives. The article compares the findings of these studies with broader research on L2 speech learning, markedness, orthographic influence, and the perception-production interface. The earlier study reported higher production than perception for /θ/, /ð/, /s/, and /z/, whereas the broader dissertation found that perception exceeded production across six fricatives. This apparent inconsistency is interpreted not as a contradiction, but as evidence that the perception-production relationship is sensitive to task design, phoneme scope, learner background, and the salience of orthographic information. The analysis argues that markedness affects Uzbek learners’ production more strongly than perception, while near-sound availability and Uzbek orthographic transparency shape both substitution patterns and perceptual confusion. The article also discusses methodological development from a narrow interdental-fricative focus to a broader fricative-system approach, highlighting how Uzbek EFL pronunciation research has evolved from identifying errors toward explaining acquisition mechanisms. The paper concludes with implications for pronunciation teaching, curriculum design, and future research in Uzbekistan